Electrical Resistances of Corn Root Segments - Anderson, W. P. (1976)
Longitudinal electrical resistances have been measured on 2-centimeter segments of corn (Zea mays L.) roots, cut at varying distances from the root apex. The segment resistances vary from 400 to 100 kilohms per centimeter along the root length (apex to 18 cm), with the maximum occurring in the 2- to 4-centimeter segment, and decreasing thereafter toward the root base. Measurements of isolated root cortical sleeves and steles show that the pathway of least resistance is in the cortex, which has a greater cross-sectional area; the specific resistance of the older stele is less than that of the cortex. The anatomical state of the xylem cannot be inferred from electrical resistance determinations.